PENGELOLAAN KONSUMSI MENUJU KETAHANAN PANGAN RUMAH TANGGA - Sri Marwanti (Universitas Sebelas Maret, 2007)
Macro food availability which do not enough guarantee household food security especially lower earn household. Lower earn household to use more than half of the earning to buy food with more than half to buy fundamental food of rice at storey level consume less than AKG and PPH.